Limitations of the Oriented Difference of Gaussian Filter in Special Cases of Brightness Perception Illusions. (March 2016) - Bakshi, Ashish; Roy, Sourya; Mallick, Arijit; Ghosh, Kuntal
The Oriented Difference of Gaussian (ODOG) filter of Blakeslee and McCourt has been successfully employed to explain several brightness perception illusions which include illusions of both brightness–contrast type, for example, Simultaneous Brightness Contrast and Grating Induction and the brightness-assimilation type, for example, the White effect and the shifted White effect. Here, we demonstrate some limitations of the ODOG filter in predicting perceived brightness by comparing the ODOG responses to various stimuli (generated by varying two parameters, namely, test patch length and spatial frequency) with experimental observations of the same.